Comparative Analysis of Effect of Lidocaine and Adrenaline Soaked Gauze Versus Normal Saline Soaked Gauze at Skin Graft Donor Site of Thigh: A Randomized Control Trial - Zahid, Zaara; Hyder Ali; Roqayyah Munawwer Khursheed; Shaikh, Unza; Sindhu Khan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the hemostatic effect of Lidocaine and Adrenaline soaked gauze with normal saline soaked gauze at skin graft donor site of thigh.Study Design: Randomized control trial (Trial ID: NCT04344483).Place and Duration of Study: Plastic & Reconstructive Surgery Department, Dow University of Health Sciences Dr. Ruth K.M. Pfau Civil Hospital, Karachi Pakistan, from Jun to Oct 2020.Methodology: A randomized controlled trial was carried out on 60 Patients under treatment in burn surgery unit. Patients were randomly assigned to 2 groups. Patients in both groups at donor sites received subcutaneous infiltration for 10 minutes, either with 2% Lidocaine and 1:100,000 Adrenaline soaked gauze or with normal saline soaked gauze. Outcomes included intraoperative bleeding, number of dressings required in first 24 hours after surgery, post-operative pain in first 24 hours, systemic analgesia requirement after surgery within 24 hours and donor-site epithelization at 14th post-operatively. Statistical Package for Social Sciences version 25 was used to analyze the data.Results: out of 60 patients, the mean age was estimated as 36.58±12.42 years and 44(73.3%) patients were males while 16(26.7%) were females. Statistically significant difference was observed in number of dressings (p=0.001), mean pain score in first 24 hours (p=0.001), intra-operative bleeding (p=0.001) and systemic analgesia requirement in 24 hours of surgery (p=0.001) between both groups.Conclusion: In comparison to normal saline soaked gauze, the Lidocaine and Adrenaline soaked gauze was effective in terms of number of dressings, pain in first 24 hours, intra-operative